EXPERIMENT-BASED DETERMINATION of DC MOTOR PARAMETERS and OPTIMIZATION of PARAMETER DETERMINATION RESULTS - (:unkn) unknown (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2012)
In this study, the results of real time estimation and calibration of a brushed wound-pole DC motor parameters are presented. An Electrical Machines Test Bed, a DC motor with a driver and a data acquisition card (DAQ) installed computer are used in the experiment setup. For experimental part of the study, the software application is developed on Matlab-Simulink platform, using Real-Time Windows Target toolbox. Experiments and measurements are made; initially, to gather information regarding the driver and sensors present in the experimental setup and then, to estimate the motor parameters by using ordinary differential equations. The experiment results are examined and estimated parameters are applied to the model created on Simulink to simulate the motor behavior. For the purpose of testing the accuracy of estimated parameters, a sample input data-set is created and concurrently applied both to simulation model and real system. In order to observe the exact harmony between the simulation and real-system responses, estimated motor parameters are calibrated using Matlab-Parameter Estimation tool and as a result, verisimilitude linear model of the DC motor is acquired. For today, DC motor can easily be found and sample component in system modeling studies, this study is presented in such a manner that both researchers and educators can easily follow it up.
Keywords: dc motor; parameter determination; parameter estimation; modeling; model simulation; IDENTIFICATION